Charge-trapping memory based on tri-layer alumina gate stack and InGaZnO channel. (9th April 2020) - Ma, Pengfei; Gao, Jiacheng; Guo, Wenhao; Zhang, Guanqun; Wang, Yiming; Xin, Qian; Li, Yuxiang; Song, Aimin
Abstract: Amorphous InGaZnO (IGZO) charge-trapping memory (CTM) devices have been designed and demonstrated entirely with thin-film technologies. All three key layers for blocking, charge-trapping, and tunneling in the gate stack are made by Al2 O3 grown by atomic-layer deposition but with different oxygen sources, i.e. O3 or deionized H2 O, to achieve different properties. X-ray photoelectron spectroscopy reveals that few defects exist in the H2 O–Al2 O3 film with only Al–O bonding, while more residual C-related impurities appear in the O3 –Al2 O3 film leading to a high density of defects, which serve as the charge-trapping states in the gate stack of the CTM devices. The fabricated IGZO CTM can be programmed under a positive voltage bias, and a large memory window of 8.2 V can be obtained with a programming voltage of +20 V. Multi-level storage has been achieved in the fabricated IGZO CTM, and a 1.9 V wide margin between the adjacent two states could be maintained for more than 10 years according to the trend of the data. With light illumination, the memory device can be erased entirely under a negative bias of −5 V. The IGZO CTM devices may have promising potentials for multi-level-storage nonvolatile memory applications based on thin-film technologies.